β1-Integrin and integrin linked kinase regulate astrocytic differentiation of neural stem cells. - Liuliu Pan; Hilary A North; Vibhu Sahni; Su Ji Jeong; Tammy L Mcguire; Eric J Berns; Samuel I Stupp; John A Kessler (PLoS ONE, 2014)
Astrogliosis with glial scar formation after damage to the nervous system is a major impediment to axonal regeneration and functional recovery. The present study examined the role of β1-integrin signaling in regulating astrocytic differentiation of neural stem cells. In the adult spinal cord β1-integrin is expressed predominantly in the ependymal region where ependymal stem cells (ESCs) reside. β1-integrin signaling suppressed astrocytic differentiation of both cultured ESCs and subventricular zone (SVZ) progenitor cells. Conditional knockout of β1-integrin enhanced astrogliogenesis both by cultured ESCs and by SVZ progenitor cells. Previous studies have shown that injection into the injured spinal cord of a self-assembling peptide amphiphile that displays an IKVAV epitope (IKVAV-PA) limits glial scar formation and enhances functional recovery. Here we find that injection of IKVAV-PA induced high levels of β1-integrin in ESCs in vivo, and that conditional knockout of β1-integrin abolished the astroglial suppressive effects of IKVAV-PA in vitro. Injection into an injured spinal cord of PAs expressing two other epitopes known to interact with β1-integrin, a Tenascin C epitope and the fibronectin epitope RGD, improved functional recovery comparable to the effects of IKVAV-PA. Finally we found that the effects of β1-integrin signaling on astrogliosis are mediated by integrin linked kinase (ILK). These observations demonstrate an important role for β1-integrin/ILK signaling in regulating astrogliosis from ESCs and suggest ILK as a potential target for limiting glial scar formation after nervous system injury.